Shifting assessment paradigms in South African higher education: Evolving towards transformative approaches to policy development. - Danica Sims; Samuel Lundie; Simone Titus; Rajendran Govender (SOTL in the South)
Assessment policies facilitate the optimisation of learning and academic performance through the provision of fair, equitable, and standardised criteria for evaluation. In recent years, the assessment policies of three South African universities have been reviewed. These policies, in comparison to their previous iterations, are indicative of transformative approaches taken in assessment practices in South Africa amid broader disruptions to higher education. This article explores shifts in assessment paradigms in South African higher education using a conceptual framework of positivist and behaviourist, interpretative and constructivist, and socio-constructivist views. Document analysis identifies several notable trends, including a shift in the purpose of assessment away from assessment of learning to assessment for learning and assessment as learning. The paradigm shift is characterised by changes in the approach from a rules-based, with specific prescriptions, to principles and values-based approaches. The growing use of alternative and technology-enhanced online assessment methods, along with the need for flexibility, are more prominent additions to these new policies post-COVID-19. However, being mindful of the South African context, culturally sensitive and fair assessment practices, that consider the diversity of South African learners, and the role of assessment in promoting equity, social justice, and quality learning, are highlighted.